2008
DOI: 10.1007/s10071-008-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

What–Where–When memory in magpies (Pica pica)

Abstract: Some animals have been shown to be able to remember which type of food they hoarded or encountered in which location and how long ago (what-where-when memory). In this study, we test whether magpies (Pica pica) also show evidence of remembering these different aspects of a past episode. Magpies hid red- and blue-dyed pellets of scrambled eggs in a large tray containing wood shavings. They were allowed to make as many caches as they wanted. The birds were then returned either the same day or the next day to ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 27 publications
3
81
0
1
Order By: Relevance
“…The ability to remember important contextual information about food sources, including their exact location and safety of access, is clearly advantageous to animals foraging in the wild; and it has been shown that rats and magpies possess such ability (9,10). It is also well established that stress hormones activated by emotional arousal enhance memories of cues associated with the arousal (11,12).…”
mentioning
confidence: 99%
“…The ability to remember important contextual information about food sources, including their exact location and safety of access, is clearly advantageous to animals foraging in the wild; and it has been shown that rats and magpies possess such ability (9,10). It is also well established that stress hormones activated by emotional arousal enhance memories of cues associated with the arousal (11,12).…”
mentioning
confidence: 99%
“…The question then was whether they could remember all three components together. Although there is now considerable evidence that a range of animals have episodic-like memory, including rats (Babb & Crystal, 2005), magpies (Zinkivskay et al, 2009), chickadees (Feeney et al, 2009), and meadow voles (Ferkin et al, 2008), issues over designing an appropriate experiment continue to plague this field. The most systematic difficulty concerns the 'when' component, with differing groups defining this in different ways (e.g., including a place in a sequence: Ergorul & Eichenbaum, 2004; a time of day: Zhou & Crystal, 2009; and using "which" instead of "when": Eacott, Easton, Zinkivskay, 2005;Eacott & Norman, 2004).…”
Section: Figure 3 Photographs Showing the Elevated Feeder (To Deter mentioning
confidence: 99%
“…Food storing did, however, lead to perhaps the greatest recent flurry of excitement and effort in comparative cognition (Clayton & Dickinson, 1999): the examination of cognitive abilities in corvids. Subsequent work is now ranging from examination of episodic-like memory in a number of species including rats (Babb & Crystal, 2005), magpies Pica pica (Zinkivskay, Nazir, & Smulders, 2009), chickadees Poecile atricapillus (Feeney, et al, 2009), hummingbirds (Henderson, Hurly, Bateson, & Healy, 2006a), and meadow voles Microtus pennsylvanicus (Ferkin, Combs, Delbarco-Trillo, Pierce, & Franklin, 2008) to examination of problem-solving in a variety of contexts, typically by corvids but not always (Auersperg, Huber, & Gajdon, 2011;Dally, Emery, & Clayton, 2010;Schmidt, Scheid, Kotrschal, Bugnyar, & Schloegl, 2011;Taylor, Elliffe, Hunt, & Gray, 2010;Teschke & Tebbich, 2011;Weir, Chappell, & Kacelnik, 2009). …”
mentioning
confidence: 99%
“…Indeed, the caching or hiding of food items for later consumption is widespread among birds and mammals [12], and different species may use different tactics shaped by the different ecological challenges that they face [13]. Food-caching corvids-birds in the crow family that includes the ravens, magpies and jays-for example, cache perishable foods such as worms as well as non-perishable nuts, and these birds can remember not only where they cached the various food items, but also how long ago, thus enabling them to recover the perishable foods before they have become degraded and inedible (see Clayton & Dickinson [14] and Zinkivskay et al [15], reviewed in Grodzinski & Clayton [16]). By contrast, squirrels solve the problem of perishability in a different way, by only caching the non-perishable nuts [17].…”
Section: Relation To the Scatter-hoarding Literaturementioning
confidence: 99%